Handbook of research on e-learning standards and interoperability frameworks and issues - Lazarinis, Fotis; Green, Steve 1957-; Pearson, Elaine 1957- (Information Science Reference, 2011)
"This handbook promotes the discussion and solutions for increasing the interoperability of future standalone and Web-based educational tools, specifically focusing on content reusability and interoperability"--Provided by publisher.